Strengthening Resilience by thinking of Knowledge as a Nutrient that connects the personal to global thinking - Bazely, Dawn; Klenk, Nicole Lisa; Perkins, Patricia E. (Ellie); Duailibi, Miriam (2014)
Poster presented at the Adaptation Futures Conference, the Third International Climate Change Adaptation Conference, Fortaleza Ceará, Brazil, May 12-16,2014. http://adaptationfutures2014.ccst.inpe.br Poster presented at the Adaptation Futures Conference, the Third International Climate Change Adaptation Conference, Fortaleza Ceará, Brazil, May 12-16,2014. http://adaptationfutures2014.ccst.inpe.br In April 2009, we held an international conference at York University, Toronto, Canada. Activists and academics who work with NGOs from the Global South and North came together to discuss adaptation to climate change. Most significantly, the Canadian perspective was entirely presented by First Nations and Inuit, which was and is highly unusual at conferences of this kind that are held in the south of Canada. This conference triggered and reinforced a cascade of diverse activities and research that has followed many intertwining pathways that diverged, crossed and reconnected over time. Several key factors have emerged from both the field experiences shared at the conference, and the related research, indicating that the adaptive capacity of disenfranchised peoples in Brazil, India, South Africa, Canada and beyond, is enhanced by diverse kinds of shared knowledge. York University & Environment Canada, Government of Canada International Polar Year for funding